PSYCHOLOGICAL RESISTANCE OF YOUNG PEOPLE TO THE INFLUENCE OF MANIPULATIONS IN ADVERTISING CONTENT: AN EMPIRICAL STUDY (Psychology Travelogs, 2025)
The article deals with an urgent psychological and socio-cultural problem - the manipulative influence of advertising on the minds of students in a post-industrial society. In the digital era, advertising has lost its purely informative character and increasingly performs the function of imposing certain behaviors, consumer attitudes, aesthetic ideals, and even moral guidelines. The purpose of this paper is to analyze the impact of advertising technologies on the psycho-emotional sphere of students, in particular their ability to critically comprehend information content and maintain independence of thought. The study is based on empirical data obtained through a survey of 60 students of Pavlo Tychyna Uman State Pedagogical University. Diagnostic tools were used, including a hypnotizability scale and tests of emotional reaction to visual advertising triggers.The results show that there is a clear correlation between the level of personality suggestibility and susceptibility to advertising messages. Most respondents do not realize the depth of the impact of advertising on their consumer habits, values, and even self-esteem. It was found that regular consumption of advertising forms a stereotypical idea of success, beauty, and happiness among students, which in some cases can lead to frustration, anxiety, and dependence on external approval.The author emphasizes the importance of an interdisciplinary approach to solving this problem, including the integration of psychology, pedagogy, media education, and advertising ethics. In the future, it is planned to expand the research with the participation of students from other universities and study the impact of political advertising.
Keywords: psychological stability; manipulative influence; advertising content; empirical research; advertising; suggestion; hypnotism